The Functional Role of Islamic Education Learning Based on the Merdeka Curriculum on Students' Tolerance and Harmony Values at SMP PGRI Kasihan - Alfarizi, Ahmad Faroch; Widodo, Hendro (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2024)
Undoubtedly, Islamic Education (PAI) plays an important role in helping people to realize the value of tolerance and harmony, especially for school-age children. Therefore, this research is intended to reveal the extent to which the role of PAI based on the merdeka curriculum that is currently rolling on the value of tolerance and harmony of students. This research uses a qualitative methodology combined with a case study approach strategy, thus making PGRI Kasihan Junior High School as the research subject. The results revealed that PAI learning based on the merdeka curriculum at SMP PGRI Kasihan raises the value of tolerance and harmony in the form of collaboration, care, and openness to the opinions of others. In this case too, the merdeka curriculum used is very helpful, through teachers and learning media that do not bore students, and make it easier to implement the values of tolerance and harmony learned.